(3aj Yde GdQLGds - (3MSjf Hf eMeO GdMSjfjs
(3ChdgG (B:s
(3HSe Gddg (B... (3Cf gPG ecJhH aj Yde GdQLGd heCNhP ef aMhd GdQLGd MQQJg JPcQI dfaSj hdYV GdeSdejf ef GdCMHGH hQJHJg Ydi ebOeI hNGJeI hCHhGH ; GdebOeI aaj MO GdYde hehVhYg hZGjJg hMOI eG jHMK ajg (B...s
(3BNQgG (B:s
... (3Cf Pdc CeGQI ef GdCeGQGJ Hd CbhGgG hdG jHYO YOI GdNHQ HGYJHGQg cGdUMjM Hd bGd hMjO YUQg aj GdahGFO GdQLGdjI hYfOj Cf QhGjI gDdGA EPG UMJ Edjge dG JfbU ef CcKQ GdUMGM (B... (3Jes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs